Identifying Entrustable Professional Activities for Shared Decision Making in Postgraduate Medical Education: A National Delphi Study. (January 2021) - Baghus, Anouk; Giroldi, Esther; Muris, Jean; Stiggelbout, Anne; van de Pol, Marjolein; Timmerman, Angelique; van der Weijden, Trudy
Abstract : Purpose: Although shared decision making (SDM) is considered the preferred approach in medical decision making, it is currently not routinely used in clinical practice. To bridge the transfer gap between SDM training and application, the authors aimed to reach consensus on entrustable professional activities (EPAs) for SDM and associated behavioral indicators as a framework to support self-directed learning during postgraduate medical education. Method: Using existing literature on SDM frameworks and competencies; input from an interview study with 17 Dutch experts in SDM, doctor–patient communication, and medical education; and a national SDM expert meeting as a starting point, in 2017, the authors conducted a modified online Delphi study with a multidisciplinary Dutch panel of 32 experts in SDM and medical education. Results: After 3 Delphi rounds, consensus was reached on 4 EPAs—(1) the resident discusses the desirability of SDM with the patient, (2) the resident discusses the options for management with the patient, (3) the resident explores the patient's preferences and deliberations, and (4) the resident takes a well-argued decision together with the patient. Consensus was also reached on 18 associated behavioral indicators. Of the 32 experts, 30 (94%) agreed on this list of SDM EPAs and behavioral indicators. Conclusions: The authors succeeded in developing EPAs and associated behavioral indicators for SDM for postgraduate medical education to improve the quality of SDM training and the application of SDM in clinical practice. These EPAs are characterized as process EPAs for SDM in contrast with content EPAs related to diverse medical complaints. A next step is the implementation of the SDM EPAs in existing competency-based workplace curricula. Abstract : Supplemental Digital Content is available in the text.